Measuring Service Quality Effect on Consumer Purchase Intention in Retailing - Singh, Dr. Trilok Pratap (International Journal of Modern Agriculture, 2020)
The objective of this research is to measure the impact of service quality on consumer purchase intention in the retail environment. Implicitly, natural and informative focus has an effect on the customer’s buying intentions. For qualitative analysis, data were collected from 477 customer surveys in large retail stores. The findings of the study indicate that quality of service have a positive effect on the purchase intention of the consumer. The results also showed that consumers do not intervene with pricing in large retail stores, as consumers feel that fair pricing are charged by retailers. Most consumers depend on the reputation and efficiency of the service quality.